Partisans of Allah: Jihad in South Asia - Jalal, Ayesha (Harvard Univ. Press, 2008)
Jihad as ethics, Jihad as war -- Jihad in precolonial South Asia -- The martyrs of Balakot -- Jihad in colonial India -- Jihad as anticolonial nationalism -- Islam subverted? Jihad as terrorism -- Conclusion